Studi pemanfaatan ruang dan kejadian banjir di wilayah pesisir Kota Dumai - Diego Ariesta Lintano; Mubarak Mubarak; Sigit Sutikno (Pelantar Press, 2017)
Environmental change due to development processes, such as land clearing and construction of settlements and industries, are belived to cause disruotion of hydrologic conditions, increases level flow and flood peak flow. It happens because of the water absorption capacity at the land surface reduced. The menthod used is frequency analysis to determine the expected local rainfall on various repeated periods and the rain intensity, which are needed for flood flow calculations. The space utilization on economic sector in Sudirman Kota Dumai Rd., are likely to be increased from 2001, 2011, ro 2015. The result of the flood flow (Qp) analysis on 2015 shows tendency to increase on the following years (Qexisting kurang dari Qprediction). Where as the result of the flood flow (Qp) with catchment well is Qeksisting lebih dari Qscenario.